A trait‐mediated, neighbourhood approach to quantify climate impacts on successional dynamics of tropical rainforests. (February 2016) - Uriarte, María; Lasky, Jesse R.; Boukili, Vanessa K.; Chazdon, Robin L.
Summary: Second‐growth forests account for 40% of the terrestrial forest carbon sink and represent the dominant forest cover in tropical regions. Uncertainties in predicting responses of these ecosystems to climate change arise from high tree species diversity, complex links between eco‐physiology and demography, and the role of ontogeny and competition in mediating individual tree responses to climate. The dynamic nature of second‐growth forests adds further uncertainty to our ability to quantify the relative importance of climate in mediating successional trajectories. To address these uncertainties, we develop a hierarchical Bayesian neighbourhood modelling approach that quantifies how the joint response of two key functional axes, wood density and specific leaf area (SLA), modulate impacts of inter‐annual variation in seasonal water stress (number of days during dry season > 1 kPa vapour pressure deficit) and night‐time temperature on growth and survival of small (5–10 cm dbh) and large (≥ 10 cm dbh) trees for 171 rainforest species in 6 s‐growth and 2 old‐growth 1‐ha mapped stands. We use model results to examine potential climate impacts on the successional trajectories of these stands. High water stress reduced large tree growth but favoured growth of small trees. Drought also reduced tree survival for both large and small trees. Tree species with high wood density suffered lower growth reductions and had higher survival under water stress. High SLA magnified the negative effects of water stress on tree growth and survival. Across all tree sizes, high night‐time temperatures did not influence growth or survival. Simulated successional trajectories under different climate scenarios using these results suggest that multi‐annual droughts will have substantial impacts of the successional trajectories of tropical forests, leading to lower stem numbers, basal area and biomass. Sustained drought will also shift functional composition of second‐growth forest by favouring species with low SLA which tend to dominate in late stages of succession. By incorporating trait‐mediated effects on key drivers of tree demography and successional dynamics, our approach provides an integrated perspective on interspecific variation in vulnerability to drought and consequences for successional trajectories in tropical rainforests. Our results suggest that multi‐annual drought stress will significantly alter structure, composition and dynamics of second‐growth forests and, from a functional perspective, accelerate succession. However, this effect may be hampered by dispersal limitation of old‐growth species into second‐growth forests. Abstract : Lay Summary